Genuine splenic artery aneurysm rupture treated by N‐butyl cyanoacrylate and metallic coils under resuscitative endovascular balloon occlusion of the aorta. Issue 3 (11th January 2016) - Aoki, Makoto; Hagiwara, Shuichi; Miyazaki, Masaya; Kaneko, Minoru; Murata, Masato; Nakajima, Jun; Ohyama, Yoshio; Tamura, Jun'ichi; Tsushima, Yoshito; Oshima, Kiyohiro
Abstract : Case: A 66 year‐old woman who presented with sudden lower abdominal pain was transferred to our emergency room. Vital signs were stable on arrival at the hospital, but immediately became unstable. Systolic/diastolic blood pressure and heart rate were 66/33 mmHg and 70 b.p.m., respectively. Computed tomography scanning showed splenic artery aneurysm rupture and extravasation. The patient was treated non‐operatively and definitively by endovascular therapy comprising resuscitative endovascular occlusion of the aorta for hemodynamic control, N‐butyl cyanoacrylate, and metallic coils as an embolization material. Outcome: On admission day 3, she was enrolled in another department and admission day 54, she was discharged. Conclusion: Although resuscitative endovascular occlusion of the aorta and N‐butyl cyanoacrylate is known to be effective, the use of resuscitative endovascular occlusion of the aorta with transcatheter arterial embolization and N‐butyl cyanoacrylate for non‐traumatic bleeding has not previously been reported. By combining and adapting these devices, their applications in endovascular management may be increased.